Vase Life and Root Propagation of Geraldton Wax (Chamelaucium spp.) Cut Flowers Treated with Glyphosate - Seaton, K.; Lee, K.; Tan, Beng (Korean Society for Horticultural Science, 2010)
Glyphosate [N-(phosphonomethy)glycine] as Roundup® (360 gㆍL⁻¹ a.i.) can render cuttings taken from cut flowers inert and unable to be propagated. It may also affect other plant physiological processes such as the vase life. In this study the effects of glyphosate on vase life and root propagation of cutting taken from cut flowers of Geraldton wax varieties ‘Purple Pride’ (Chamelaucium uncinatum), and ‘Bridal Pearl’ and ‘Albany Pearl’ (C. uncinatum × C. megalopetalum hybrids) were investigated. Cuttings of ‘Purple Pride’ pulsed in a 0.1% Roundup® (0.36 gㆍL⁻¹ glyphosate) solution for 20 minutes failed to produce roots and were dry within 28 days; leaf vase-life also increased by three days with no adverse effect on flower vase life, normally evidenced by accelerated senescence and petal closure. Pulsing in a 1% Roundup® (3.6 gㆍL⁻¹ glyphosate) or 10% Roundup® (36 gㆍL⁻¹ glyphosate) solution for 20 minutes increased flower vase life by 3 to 5 days. Pulsing in Roundup® solutions for longer durations at these concentrations did not decrease flower vase life below the control, but leaf vase life was reduced from 10 days (control) to between 4 (1% Roundup® 120 minutes) and 7 days (10% Roundup® for 60 minutes).A similar result was also found for ‘Bridal Pearl’ except that there was no improvement in flower vase life following a 20 minute pulse in a 0.1% Roundup® solution. No roots occurred in cuttings taken from flowering stems of ‘Albany Pearl’ pulsed in a 0.1% Roundup® solution for 20 minutes at 20℃ or immersed in a 0.25% Roundup® solution for one minute. There was also no reduction in vase life of flowers and leaves of sprigs taken from stems pulsed or immersed in these Roundup® solutions. A protocol using a 0.1% Roundup® solution as a 20 minute pulse or a stronger 0.25% Roundup® solution as a 1-minute immersion should provide an effective postharvest treatment to prevent propagation of cuttings taken from Geraldton wax cut flowers.